Significance of intestinal alkaline phosphatase in predicting histological activity of pediatric inflammatory bowel disease - Ateş, Burcu Berberoğlu; Talim, Beril; Gülşen, Hayriye Hizarcıoğlu; Demir, Hülya; Karaismailoğlu, Eda; Özen, Hasan; Saltık-Temizel, İnci Nur (The Turkish Journal of Pediatrics, 2022)
Background. Intestinal alkaline phosphatase (iAP) is an intestinal brush border enzyme that is one of the factors involved in the pathogenesis of inflammatory bowel disease (IBD). The aim of the study was to investigate the relationship between iAP enzyme and histological inflammatory activity in patients with IBD. Methods. A total of 44 children were enrolled in this study including IBD patients (n=24; 12 Crohn`s disease [CD] and 12 ulcerative colitis [UC]) and controls (n=20). Anti-human iAP antibody stained ileocolonoscopic biopsy specimens were graded for the terminal ileum and each section of the colon. Hematoxylin-eosin stained sections were used to determine inflammatory activity. Histopathological findings were compared in pre- and post-treatment biopsies of each group and with the control group (CG). Results. A low grade of iAP staining was detected in IBD patients compared to the CG (p=0.02). iAP was remarkably concentrated in the terminal ileum (TI) and especially in region 1, which involved the apical surface, brush border, and epithelial cells. A significant negative correlation was found between the grade of iAP staining and inflammatory activity both in pre- and post-treatment biopsies (p=0.02, p=0.008, respectively) in the terminal ileum of CD patients. Likewise, pre-treatment biopsies of UC and CD patients and biopsies of the CG were compared with each other according to the grade of iAP staining. There were significant negative correlations for CD patients compared to UC and the CG in region1 of TI, and regions 1 and 2 (lamina propria and goblet cells) of the colon (p= 0.015, p= 0.006, p < 0.001, respectively). Conclusions. As a histological marker, iAP can be of value in monitoring the histological activity of IBD, particularly in remarkable inflammation in the small intestine.